Analisis Kualitas Website terhadap User Experience pada Website Library Garden UPT Pusat Perpustakaan UIN Raden Mas Said Surakarta berdasarkan Teori Shedroff dan Teori Miller - Sutrasno, Sundari; Nurlistiani, Nurlistiani (Institut Agama Islam Negeri Salatiga, 2023)
The following research aims to find out the quality analysis carried out on the Library Garden Website on the user experience when using it. In the following research, a qualitative method is used, where the author collects data sourced from interviews, observations, and documentation. The data were then analyzed through the process of data reduction, data presentation, and conclusion drawing. Furthermore, the data was tested for validity using the credibility test with the triangulation technique method. The analysis process is carried out using two theories, namely Shedroff Theory and Miller Theory. Website quality can be determined in terms of: content, information design, performance, compatibility, visual design, and interaction design which are summarized in Shedroff Theory. Meanwhile, Miller Theory is used to represent a more specific analysis related to visual design, which consists of parts: header, feature area, body, sidebar, footer, and background. The results of the research show that the Library Garden website has a fairly suboptimal quality in presenting user experience. This is indicated by the many factors that do not match the results of the analysis of the twelve concepts according to Shedroff Theory and Miller Theory; which of course greatly affects the process of searching and disseminating information related to UPT Pusat Perpustakaan UIN Raden Mas Said Surakarta. The results of this study are expected to provide reference advice / input to the UPT Pusat Library UIN Raden Mas Said Surakarta in maximizing management strategies, development, and better utilization of the Library Garden Website in the future.